The Impact of Decree 70/2023 on Labor Regulation and Industrial Relations in Argentina: A Legal and Economic Analysis - Ntoumanis, Asbjørn Britt; Jorge, Santiago Osvaldo; Zagarese, Eduardo; Wunderlin, Alberto; Stern, Augusto Regier; Luiz, Phillip José (International Journal of Law and Public Policy (IJLAPP), 2024)
Decree 70/2023, issued by the Argentine government, addresses critical issues in labor and industrial relations amidst ongoing economic and social challenges. This study evaluates the decree’s impact on labor regulations, focusing on minimum wage standards, protection against unfair dismissal, and dispute resolution mechanisms. Utilizing a mixed-methods approach, both qualitative and quantitative analyses were conducted. Qualitative methods included legal document reviews and expert interviews, while quantitative methods involved assessing changes in wage levels, unemployment, and productivity. Key findings indicate that the decree’s increase in minimum wage aims to enhance worker welfare and stimulate economic growth, but poses challenges for employers, particularly small and medium-sized enterprises. Stricter procedures and improved compensation for layoffs are expected to reduce job insecurity and foster fairer employment practices, though these measures may raise operational costs and administrative burdens for businesses. Additionally, the new dispute resolution mechanisms, which emphasize mediation and arbitration, are designed to resolve conflicts more efficiently and transparently. However, consistent implementation and oversight remain critical challenges. The study concludes that while Decree 70/2023 represents a significant step towards better labor conditions and industrial relations in Argentina, its success will depend on rigorous enforcement and stakeholder cooperation. Further research should focus on the long-term effects of these regulations on Argentina’s labor market and economic stability, as well as continuous evaluation to refine these policies for optimal outcomes.